Analyzing Serum Eosinophil Cationic Protein in the Clinical Assessment of Chronic Rhinosinusitis. Issue 3 (May 2013) - Kim, Kyung Soo; Won, Ho-Ryun; Park, Chong Yoon; Hong, Joon Hyeong; Lee, Jae Heon; Lee, Kyu Eun; Cho, Hyun Sang; Kim, Hyun Jik
Background: Eosinophil cationic protein (ECP) is a major granule–derived protein with cytotoxic activity found in eosinophils and has been known as a useful marker of allergic inflammation. In this study, we assessed the clinical significance of ECP in chronic inflammation of the nasal mucosa by evaluating the relationship between eosinophil activity and serum ECP concentration in a cohort of subjects with or without chronic rhinosinusitis (CRS) and allergic rhinitis (AR). Methods: We retrospectively reviewed the medical records of 492 subjects and analyzed eosinophil percentage in nasal smears, serum eosinophil counts, serum ECP concentrations, symptom scores, CT scores, the size of nasal polyp, and recurrence of CRS at follow-up. Results: Elevated serum ECP concentration was closely related with higher eosinophil expression in all subject's nasal smears and sera. CRS subjects without AR had a higher percentage of immune cells that were eosinophils compared with control subjects and it was similar to subjects' with AR only or with both CRS and AR. CRS subjects without AR also had significantly higher serum ECP concentrations and eosinophil counts compared with control subjects. Additionally, serum ECP concentration was significantly correlated with CT scores, symptom scores, polyp size, and recurrence rate in CRS subjects without AR. Conclusion: Serum ECP concentration can be used as a marker of local and systemic eosinophil expression. We conjecture that although serum ECP elevation may not be specific in AR, analysis of serum ECP concentration could be particularly useful in estimating the progression and prognosis of CRS.